AN ANTHROPOCENTRIC APPROACH TO TERMS AND LANGUAGE - Matyakubova Rayhon Farkhodovna; Rakhimova Guzal Yuldashovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In linguistics, this created the need to consider the knowledge of observing the world scene as an important linguistic and cultural tool that reflects the national-mental characteristics of the nation. After all, the stagnated moral rules, values, and aspects related to the national mentality of the people, characteristic of the national mentality, are clearly reflected in the stable units of the language formed over the centuries.